Preparation and characterization of GG-LiCF3SO3-DMSO gel polymer electrolyte for potential lithium-ion battery application - Daud, N.M.A.C; Tamchek, N.; Noor, I.M. (Avanti Publishers, 2022)
This work uses gellan gum (GG) natural polymer as the base polymer to prepare gel polymer electrolytes (GPEs). Lithium trifluoromethanesulfonate (LiCF3SO3) salt is used as a charge supplier, and dimethyl sulfoxide (DMSO) acts as a plasticizer to keep the electrolyte in gel form. Two electrolyte systems are formed, which are LiCF3SO3-DMSO liquid electrolytes and GG-LiCF3SO3-DMSO GPEs. Liquid electrolyte with a composition of 12.42 wt.% LiCF3SO3-87.58 wt.% DMSO (LN3 electrolyte) revealed the highest room temperature conductivity (σrt) of 9.14 mS cm-1. The highest σrt value obtained by the LN3 electrolyte is strongly influenced by the charge carrier concentration (n) relative to the mobility (µ). To form GPEs, GG is added to the LN3 electrolyte since this sample composition gave the highest σrt. The electrolyte of 2.00 wt.% GG-12.18 wt.% LiCF3SO3-85.82 wt.% DMSO (GN3 electrolyte) showed the highest σrt of 9.96 mS cm-1. The highest σrt value obtained by GN3 electrolyte is strongly influenced by µ rather than n. The conductivity-temperature study showed that the increase in conductivity for GG-LiCF3SO3-DMSO GPEs is controlled by an increase in n, not µ. Linear sweep voltammetry (LSV) for the GN3 electrolyte showed high electrochemical stability up to 4.8 V. Cyclic voltammetry (CV) illustrated the redox process in the GN3 electrolyte is reversible. A lithium-ion battery fabricated with GN3 electrolyte showed a good discharge performance up to 480 hours with an average voltage of 1.50 V discharged at a current of 0.001 mA. Based on this work, it can be concluded that natural polymer GG-based GPE has great potential for use in LIBs as a charge transport medium.